Evaluation of optical efficiency of an all-glass ETC using ray tracing technique. (2018) - Aseri, Tarun Kumar; Sharma, Chandan; Sharma, Ashish Kumar; Misra, Rohit; Jamuwa, Doraj Kamal
Hot water is required for various industrial process heating applications and daily domestic needs in the temperature ranges of 60° to 100°. Hot water requirement in this temperature range can be effectively met using solar energy by incorporating either flat plate solar collector (FPC) or evacuated tubular solar collectors (ETC). In the present study, an attempt has been made to estimate optical efficiency of an all glass ETC using ray trace technique. Four different configurations have been considered: without reflector; with flat reflector; with V reflector and with cusp reflector. It is observed that the optical efficiency of ETC with cusp reflector was estimated to be around 85% and observed to be almost constant for various values of incidence angle of solar radiation. The other configurations were found to be significantly sensitive to incidence angle of solar radiation and provide much lower optical performance in the range of 45%-75%.